2017
DOI: 10.1016/j.jvs.2017.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of peripheral arterial disease via percutaneous brachial artery access

Abstract: Brachial access is a reliable and effective option for treatment of peripheral vascular disease and should be considered when femoral access is difficult or contraindicated and when a bypass graft is present in the femoral region. In addition, bilateral lesions may be approached easily through one brachial artery access site, making this approach advantageous when bilateral lesions are expected. The complication rate is similar to femoral access and can be minimized with ultrasound-guided access distally over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Previous studies have demonstrated minor complication (pseudoaneurysm or hematoma) rates of 2% to 14% and major complication (distal embolization; brachial artery thrombosis, dissection, or fistula formation) rates of 1.9% to 10.0% associated with brachial access. 12 , 13 , 14 In addition to access site complications, upper extremity access is also associated with an increased risk of stroke from wire manipulation within the aortic arch. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated minor complication (pseudoaneurysm or hematoma) rates of 2% to 14% and major complication (distal embolization; brachial artery thrombosis, dissection, or fistula formation) rates of 1.9% to 10.0% associated with brachial access. 12 , 13 , 14 In addition to access site complications, upper extremity access is also associated with an increased risk of stroke from wire manipulation within the aortic arch. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated minor complication (pseudoaneurysm or hematoma) rates of 2-14% and major complication (distal embolization; brachial artery thrombosis, dissection, or fistula formation) rates of 1.9-10% associated with brachial access. [12][13][14] In addition to access site complications, upper extremity access is also associated with increased risk of stroke from wire manipulation within the aortic arch. 15 The technique described here avoids the risks associated with upper extremity access or navigation of large sheaths over the "raised bifurcation" of a previously placed EVAR, allowing for the treatment of common iliac aneurysms through an entirely ipsilateral approach and J o u r n a l P r e -p r o o f preventing undue caudally directed forces on the graft bifurcation with subsequent potential migration.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…This includes prior abdominal aortic aneurysm repair, iliac tortuosity, severe aortoiliac femoral occlusive disease, ostial SFA occlusion without a stump, absent femoral pulses, and reluctance among interventionalists to access a femoral artery on the same side as an ipsilateral femoral bypass or other obstruction of the groin(eg, morbid obesity, infection, hematoma, trauma, scarring). [6][7][8][9] In these cases, when the conventional femoral approach is impractical, radial, brachial, popliteal, and pedal access have been shown to be viable alternatives. [6][7][8]10 Direct comparisons of these approaches have not been conducted in the context of lower extremity occlusive disease, and there is a lack of guidance to suggest the preferred alternative access site for SFA occlusive disease.…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular procedures have been extensively and frequently used for treating arterial system diseases. 1 Currently, the brachial artery access is more frequently used for endovascular interventions than before, 2,3 while the femoral artery access has been the preferred route for endovascular intervention historically. 4 Brachial access is considered to be a convenient and safer puncture site for aortic dissection of patients, 2,3 especially when the femoral access is precluded or other arterial interventions are required during the procedure.…”
Section: Introductionmentioning
confidence: 99%